Implementation of a Procainamide-Based Cardioversion Strategy for the Management of Recent-Onset Atrial Fibrillation. (July 2021) - Matuskowitz, Andrew J.; Weant, Kyle A.; Gregory, Haili; Field, Michael E.; Calhoun, Chara; Bushkar, Brent J.; Hall, Gregory A.; Caporossi, Jeffrey
Abstract : Atrial fibrillation/flutter (AF) remains the most common rhythm disturbance in adult patients presenting to emergency departments (EDs). Although pharmacologic cardioversion has been established as safe and effective in recent-onset AF, its use in U.S. EDs is uncommon. The purpose of this study was to assess the safety and efficacy of intravenous (IV) procainamide for pharmacologic cardioversion in patients presenting to the ED with AF of <48-hr duration. Patients presenting to the ED with recent-onset AF (<48 hr) undergoing a cardioversion strategy with IV procainamide from 2017 to 2019 were reviewed. Clinical outcomes assessed included rates of cardioversion, hospital admission, stroke, and return ED visits for arrhythmia or serious adverse events. A total of 64 patients received procainamide therapy—60.9% achieved cardioversion and 35.9% were admitted to the hospital. The mean dose was 1062.4 mg (12.1 mg/kg). No patients returned to the ED secondary to stroke and 9.4% experienced complications attributed to procainamide, the most common being hypotension. Within 30 days of therapy, 20.3% of patients returned to the ED secondary to arrhythmia recurrence. Patients experiencing cardioversion with procainamide were less likely to be admitted to the hospital (25.6% vs. 52.0%; p = 0.04) or receive a rate control agent (17.9% vs. 64.0%; p = 0.001). There was no significant difference in the rate of 30-day return between those who experienced pharmacologic cardioversion and those who did not ( p = 0.220). The implementation of a procainamide-based acute cardioversion strategy for patients presenting to the ED with recent-onset AF resulted in a 60% cardioversion rate, which was associated with a significantly higher rate of discharge from the ED. Transient hypotension was the most common adverse event. Further investigation into ED-based protocols for management of recent-onset AF is necessary to better understand their safety and efficacy.